The Relationship Between Physical Exercise and Subjective Well-Being in College Students: The Mediating Effect of Body Image and Self-Esteem - Shang, Yao; Xie, Hao-Dong; Yang, Shi-Yong (Frontiers in Psychology, 2021)
To examine the effects of physical exercise on the subjective well-being via the mediation of body image and self-esteem, then to explore the level of subjective well-being caused by varying physical activities level, and thereby to provide some suggestions on the improvement of subjective well-being by physical exercise intervention in college students. A total of 671 college students from three universities voluntarily participated in the survey. Descriptive statistics, Pearson's product-moment correlation, and mediation model analysis were conducted using SPSS statistics 19.0. The results showed that (1) the physical exercise level was positively significantly correlated with the subjective well-being level in each dimension (R=0.09~0.17，P<0.05), (2) people with the higher level of physical exercise had the higher score of overall subjective well-being or each dimension, and (3) physical exercise had completed mediation effect on the subjective well-being via body image and self-esteem. The mediation analysis revealed that it implied two paths: First, the single mediating path via body image (indirect effect=0.054, 95% CI: [0.029, 0.082]). Second, the serial mediating path via body image and self-esteem (indirect effect=0.093, 95% CI: [0.067, 0.122]). Some practical implications have been discussed on the physical exercise intervention for promoting the subjective well-being level in college students.